The value and role of land management at the local level in the development of local communities land - Kapinos, N. (Land Management, Cadastre and Land Monitoring, 2017)
Planning of land use by land - is an integral part of the management of land use, which provides a mechanism by which decisions are coordinated among various local, regional and national authorities, and helps implement social responsibilities of public authorities in the use and protection of land and other natural resources. Today, during the implementation of the decentralization of power, much attention is given to the transition from the existing centralized approach to conventional land-use planning (conventional land use planning), which the world is seen more as a institutional approach (institutional approach) to the agreed land use planning (rarticipatory land use planning), which puts the interests of the foundation rights of economic, environmental, technological and socio-cultural conditions. Accordingly, it is important to define the relationship between the components of local governance in land development and local communities to identify the main stages of its planning, which will allow to solve social and economic problems of land use while preserving the natural ecological sustainability of land and other natural resources like land development and land use planning. It is also associated with a change in the land system ofUkraineand the transition to market land relations, which requires the transition to a new system of land use and proper planning it with the realities of today. During the 2000-2016 biennium. Ukraine has experienced an unprecedented reform of collective agricultural enterprises in market-oriented agricultural farm land for the project made it possible to dramatically increase the share of agricultural land owned by agricultural cooperatives (14.5%), limited liability companies (26.4%) and private (private rental) companies (10.4%). Nearly 405,000 farmers based on their land shares (shares) created over an area of more than 1.6 mln. Ha of farmland farms. However, after the enactment of the Land Code of Ukraine (2001) power rural town councils on order, including the management of land use, land narrowed to only settlements. This led to the decline in land management activities performed. Also, due to lack of funding work on complex land use of rational use of land and their health are not implemented. This land use agricultural land use, which functioned until 1990 was destroyed, and new forms of the rational internal build area to date has not been established. According to Art. 130 Land Code of Ukraine emptive right to purchase agricultural land are citizens ofUkraine, permanently residing in the territory of the local council, where the sale of land, as well as relevant local authorities. However, the status of territory of the local council in land law is not defined. No separation of state and municipal property without development of land management projects within the areas of village councils to streamline land farms has created a number of problems of forecasting, planning and organization of rational use and protection of land at local and economic levels, and therefore financially stable communities. Thus, the importance and role of land management at the local level in the development of local communities land use at this stage of development of land relations is growing. But it needs to speed up recovery (existing before the adoption of the Land Code of Ukraine in 2001) the powers of local communities in the sphere of land relations. Keywords. Land management, land use, site councils, land reform.